(untitled) (Research, Society and Development, 2022)
This article aims to identify and analyze population demands for environmental health actions in the view of nurses from the Family Health Strategy. It is a research with a qualitative approach of the descriptive type, using the theoretical contribution of Dialectical Hermeneutics. Nineteen nurses from different Basic Health Units in a municipality of Minas Gerais were interviewed by telephone, using a semi-structured script. The data obtained were grouped into three analytical categories: “Care for the environment and prevention of problems related to waste disposal”, “Socioeconomic approach to environmental problems” and “Prevention of the spread of diseases and vectors”. As a result, it was identified that environmental problems related to the inadequate destination of solid waste, the lack of basic sanitation and issues of social vulnerability constitute demands for nursing actions in Primary Health Care. It can be inferred that there is a wide field of work for nurses in the context of environmental health, and the performance of health actions focused on this theme have a positive impact on the population’s quality of life.